The reckless oath we made - Greenwood, Bryn (G.P. Putnam's Sons, 2019)
"A provocative love story between a tough Kansas woman on a crooked path to redemption and the unlikeliest of champions, from the New York Times bestselling author of All the Ugly and Wonderful Things. Zee is nobody's fairy tale princess. Almost six-foot, with a redhead's temper and a shattered hip, she has a long list of worries: never-ending bills, her beautiful, gullible sister, her five-year-old nephew, her housebound mother, and her drug-dealing boss. Zee may not be a princess, but Gentry is an actual knight, complete with sword, armor, and a code of honor. Two years ago the voices he hears called him to be Zee's champion. He's barely spoken to her since, but he has kept watch, ready to come to her aid. When an abduction tears Zee's family apart, she turns to the last person she ever imagined--Gentry--and sets in motion a chain of events that will not only change both of their lives, but bind them to one another forever"--